PEG-PLGA nanoparticles deposited in Pseudomonas aeruginosa and Burkholderia cenocepacia - Tchatchiashvili, Tinatini; Duering, Helena; Mueller-Boetticher, Lisa; Grune, Christian; Fischer, Dagmar; Pletz, Mathias W.; Makarewicz, Oliwia (Journal of Pharmaceutical Analysis, 2024)
In our prior research, polymer nanoparticles (NPs) containing tobramycin displayed robust antibacterial efficacy against biofilm-embedded Pseudomonas aeruginosa (P. aeruginosa) and Burkholderia cenocepacia (B. cenocepacia) cells, critical pathogens in cystic fibrosis. In the current study, we investigated the deposition of a nanoparticulate carrier composed of poly(D,L-lactic-co-glycolic acid) (PLGA) and poly(ethylene glycol)-block-PLGA (PEG-PLGA) that was either covalently bonded with cyanine-5-amine (Cy5) or noncovalently bound with freely embedded cationic rhodamine B (RhB), which served as a drug surrogate. After exposing these NPs to bacteria, we performed cell fractionation and fluorescence analysis, which highlighted the accumulation of Cy5 in the outer membranes (OMs) and the accumulation of RhB in the cytoplasm (CP) of cells. The results indicated that these organic NPs are effective vehicles for targeted antibiotic delivery in bacterial cells, explaining the observed increase in the efficacy of encapsulated tobramycin against biofilms. This work emphasizes the potential of PEG-PLGA-based formulations for advanced drug delivery strategies.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Antimicrobial activity; Bacterial membrane; Cystic fibrosis; Lipopolysaccharide; Poly(ethylene glycol); Polyester; Tobramycin